Theoretical studies on the structure and stability of dimer of the parent phosphagermaallene HP=C=GeH2. - Tsan, Isabelle Xinning. (2009)
The synthesis of heroallenes, compounds in which one, two, or even three carbon atoms of an allene have been replaced by heavier elements of group 14 (Si, Ge, Sn) or 15 (P, As, Sb) have constituted a new challenge in organometallic chemistry. Due to the presence of two unsaturations, such heteroallenes are thought to possess a rich and versatile chemistry. The further coupling of two molecules of the phosphagermaallene will show to have unique structures and will prove to be interesting for both theory and experiment. The project has performed a detailed theoretical computational study on the dimer of the parent phosphagermaallene HP=C=GeH2. Low-lying isomers of the parent heteroallene have been identified and shown using various computational tools like Chem Office and the Gaussian 03 platforms. Several transition states have also been identified through the same methods. These molecules are necessary for the construction of the potential energy surface (PES) of the phosphagermaallene.